Impulse zur Stochastik in der Oberstufe - Biehler, Rolf; Binder, Karin; Haverkamp, Michael; Kempen, Leander (Mathematikabitur „Status Quo–Quo Vadis “: Tagungsband zur Fachtagung zum Mathematikabitur am 11./12. Februar 2025 in Dresden)

Organisationen, Konventionen und Kritik. Der französische Neopragmatismus in der Organisationsforschung - Knoll, Lisa (Handbuch Organisationssoziologie)

"Future Fresko" - Charlotte Kraffts Münsterland-Blog MOMUMENT als dystopische Heimatliteratur - Morrien, Rita (Literatur in Westfalen. Beiträge zur Forschung 22)

‘School is no longer a lone wolf effort’: leadership strategies for inclusive, community-based school cultures - Woodcock, Stuart; Avramidis, Elias; Sharma, Umesh; Subban, Pearl; Sahli Lozano, Caroline; Kullmann, Harry; Loreman, Tim; Wüthrich, Sergej; Knickenberg, Margarita (School Leadership & Management)
Based on the premise that the successful implementation of inclusion is largely dependent on the educators’ commitment to inclusive ideals, this study sought to examine the ways principals promote an inclusive vision and foster the development of associated practices in their school community. The study employed an exploratory qualitative research design, collecting data through semi-structured interviews and focus groups with 12 principals of highly-ranked inclusive schools from four countries: Australia, Italy, Switzerland, and Spain. In so doing, the emphasis was placed on the principals’ perspectives and practices that contribute to the development of an inclusive school culture. The iterative process of thematic analysis revealed five broad key factors that affect and impact school inclusivity, namely: institutional commitment to a collective inclusive culture; family partnership and co-responsibility; collaboration among key stakeholders (e.g. students, teachers, other staff); students’ voice and agency; and building and sustaining inter-institutional partnerships. This paper concludes by advocating a community-based approach model to school inclusion by identifying key factors on which principals can rely to navigate material, social, and political challenges.
Keywords: Inklusive Bildung; Schulentwicklung; Schulleitung; Gemeinschaftlichkeit; Haltung

Interkulturelle Pädagogik: Fallstricke, Potenziale und Forschungsgegenstände - Pöllmann, Andreas
Das Fachbuch ermutigt dazu, eingefahrene Denkweisen zu hinterfragen und neue pädagogische Handlungsspielräume zu erschließen. Es verbindet theoretische Kontroversen mit praxisnahen Fragestellungen und eröffnet so einen Zugang zu aktuellen Debatten in Bildung und Gesellschaft. Die innovativen Konzepte der kulturellen Pluriformität und der intersektionalen Interkulturalität ermöglichen differenzierte Denk- und Handlungsperspektiven jenseits vereinfachender Kulturbegriffe. Weitere Alleinstellungsmerkmale des Buches sind die reflektierte Auseinandersetzung mit einschlägigen Fallstricken, Potenzialen und Forschungsgegenständen sowie die konsequente Einbeziehung englischsprachiger und spanischsprachiger Fachliteratur. Das komplexe Feld wird nicht vereinfacht, sondern in seiner Widersprüchlichkeit und Vielschichtigkeit ernst genommen. Dabei lädt das Buch dazu ein, pädagogische Routinen kritisch zu reflektieren, vermeintliche Selbstverständlichkeiten zu irritieren und solidarisches Handeln zu fördern. Es bietet Impulse für eine emanzipatorische interkulturelle Pädagogik, die zu Multiperspektivität, Gerechtigkeit und solidarischem Zusammenleben beiträgt.

BBNE funktioniert nicht allein - Hartwich, Katharina (Berufsbildung)

Wer plündert, wird erschossen - de Gruisbourne, Birte (Deutsche Zeitschrift für Philosophie)

Perspektiven solidarischer Erhaltungslust - de Gruisbourne, Birte (Zeitschrift für Medienwissenschaft)

AnnoPy – Potenziale von KI-basierter Learning Analytics für die Förderung wissenschaftlicher Textkompetenz - Scholle, Oliver; Rezat, Sara; Rezat, Sebastian; Niehus, Dominik (Learning Analytics, Artificial Intelligence und Data Mining in der Hochschulbildung: Beiträge zur Learning AID 2025)
AnnoPy ist ein digitales Werkzeug, um kollaborativ Texte zu lesen, zu erschließen und zu analysieren. Es ist für die Präsenzlehre konzipiert und unterstützt Lehrende dabei, den Übergang von der individuellen Auseinandersetzung mit wissenschaftlichen Texten hin zu einer kollaborativ-sozialen Aushandlung des Gelesenen in Lehrveranstaltungen zu organisieren und zu strukturieren. Im Beitrag wird das digitale kollaborative Tool AnnoPy vorgestellt und gezeigt, welche Potenziale sich für die Analyse von Daten über Lernende durch die Integration von KI-basierter Learning Analytics in das Tool ergeben. Anhand von exemplarischen Daten aus einer Vorlesung der Mathematikdidaktik wird zunächst vorgestellt, wie in AnnoPy eine algorithmisch-händische Analyse und Datenauswertung erfolgte, um dann diese Art der Auswertung mit einer KI-gestützten Auswertung, bei der ein MCP-Server eingebunden wurde, zu vergleichen.

Students’ mathematical feedback processes using a digital curriculum resource: A qualitative perspective - Rezat, Sebastian (ZDM – Mathematics Education)
This qualitative case study investigates how automated feedback from a widely accessible digital curriculum resource influences students’ mathematics learning. Drawing on a dialogic feedback framework, the study analyzes students’ feedback processes in an ecologically valid learning context. Grounded in a sociocultural perspective, the framework integrates Carless’ dialogic conceptualization of feedback, Shute’s feedback typology, and Vergnaud’s scheme theory. Eight eighth-graders from a German secondary school worked individually on percentage problems at home, video-recorded via online conferencing. Data included screen recordings and think-aloud protocols, which were analyzed using qualitative text analysis. Results reveal large individual differences in feedback processes—students vary in when and how they access feedback messages and how they make sense of them. Successfully solving a task after feedback does not always indicate understanding; in some cases, feedback aided procedural completion without conceptual insight. The effectiveness depended on the alignment between task design, feedback message content, and students’ actual difficulties. The study concludes that qualitative analysis of feedback processes with digital technologies in ecologically valid settings is necessary to target specific student difficulties and promote learning.

Private Peers’ Disclosure Transparency and Public Firms’ Information Environment - Beyer, Bianca; Flagmeier, Vanessa; Kosi, Urska
This study examines how private peers’ disclosure transparency affects public firms’ information environment, captured through analyst forecast behavior. Focusing on the most important private firms operating in U.S. industries, we investigate whether private peer disclosure—despite differing substantially from public firm disclosure—is incorporated into analysts’ forecasts. In a cross-sectional analysis, we document lower forecast quality in industries where private peers’ disclosure intensity is low. In contrast, when private peers’ disclosure intensity is high, forecast quality does not differ from that in industries with only public peers. We find consistent results for a subsample of U.S. private peers. Consistent with this interpretation, a difference-in-differences analysis documents increased analyst forecast activity around the disclosure dates of private peers. Together, these findings indicate that analysts incorporate private peers’ information when these peers are both economically important and sufficiently transparent, and highlight that variation in private firms’ disclosure intensity generates heterogenous externalities for public firms. Overall, our evidence supports a cost-benefit trade-off in analysts’ information acquisition, and, by documenting the relevance of private peers’ information for public firms, contributes to the debate on the externalities of private firms’ disclosure transparency.

Poiesis des Selbst. Eine raumtheoretische Bestimmung des ‚Devianz-Orts‘ anhand von Analysen zu Lutz Seilers Romanen «Kruso» und «Stern 111» - Heerdegen, Björn

The spatial and sectoral incidence of Germany’s COVID-19 insolvency gap - Rahali, Mahdi; Kosi, Urska; Gassen, Joachim

Dissemination of information by small caps - Böing, Dennis; Kosi, Urska

Exploring serum biomarkers in paediatric psychiatry: the impact of NfL and GFAP - Pawlitzki, Marc; Masanneck, Lars; Schlarbaum, Laura; Jankovic, Nicole; Bittner, Stefan; Steffen, Falk; Kuhle, Jens; Benkert, Pascal; Repple, Jonathan; Bühlmeier, Judith; Hinney, Anke; Hebebrand, Johannes; et al. (Translational Psychiatry)
Abstract Serum neurofilament light chain (sNfL) and glial fibrillary acidic protein (GFAP) are biomarkers of neuroaxonal and astrocytic damage but remain understudied in adolescent psychiatric populations. This study investigated sNfL and GFAP levels in 412 adolescents diagnosed with anorexia nervosa (AN) ( n = 52), depression ( n = 237), and other psychiatric disorders ( n = 123). We assessed their diagnostic utility, correlation with disease severity, and longitudinal changes during AN treatment. Biomarkers were measured using Single Molecule Array technology, with Z-scores derived from reference datasets. Compared to population norms, both biomarkers were elevated in AN (sNfL: 1.15 ± 1.17; GFAP: 1.50 ± 0.84) and in depression (sNfL: 0.34 ± 1.10; GFAP: 0.58 ± 1.00). Patients with AN showed significantly higher biomarker levels than those with depression or other psychiatric disorders; importantly, this distinction remained evident in sensitivity analyses restricted to underweight individuals with depression. In AN, sNfL levels correlated with baseline weight loss (β = −0.45, R² = 0.20) and declined significantly during treatment, while GFAP changes were less pronounced. Neither marker correlated with depressive symptom severity. Bootstrapped ROC analyses showed moderate-to-good discriminatory power (AUCs 0.70–0.84) for distinguishing AN from depression. These findings suggest that neuroaxonal and astrocytic stress is a component of adolescent psychopathology, particularly in AN. sNfL appears sensitive to starvation-related neurobiological changes, with levels normalizing alongside weight restoration. GFAP showed similar but less robust trends. Accordingly, the observed biomarker changes reflect more than underweight alone, supporting a potential role in differential diagnosis and treatment monitoring.

Vitamin D, inflammation and depressive symptoms in adolescents: analysis using observational and interventional data - Schlarbaum, Laura; Jankovic, N.; Engler, H.; Hirtz, R.; Grasemann, C.; Peters, T.; Hinney, A.; Antel, J.; Hebebrand, J.; Föcker, M.; Libuda, Lars (Neuroscience Applied)

Kulturelles Lernen im Fremdsprachenunterricht unterstützen - Frankemölle, Bernd (Die Wirksamkeit von Lehr-/Lernmethoden im Fremdsprachenunterricht. Empirische Befunde für Lehrkräfte und Unterricht)

The role of digital teaching experience for learning about digital as well as inter- and transcultural foreign language teaching in a web-based training - Frankemölle, Bernd; Göbel, Kerstin (Digital and AI Competence in Subject-Specific Education)

Double Hall algebras and derived equivalences revisited - Burban, Igor; Perniok, Daniel
Let $\mathbb{k}$ be a finite field and $\mathcal{A}, \mathcal{B}$ be $\mathbb{k}$-linear $\mathsf{Ext}$-finite hereditary abelian categories. A theorem of Cramer asserts that, under suitable assumptions, a derived equivalence $\mathcal{D}^b(\mathcal{A}) \!\longrightarrow\! \mathcal{D}^b(\mathcal{B})$ between two such categories induces an algebra isomorphism of the corresponding double Hall algebras $\mathsf{DH}_\mathcal{A} \!\longrightarrow\! \mathsf{DH}_\mathcal{B}$. It turns out that a counting formula for certain distinguished triangles in $\mathcal{D}^b(\mathcal{A})$, on which Cramer's proof relies, is incorrect in general. We give a corrected proof of Cramer's theorem which preserves the overall strategy of his approach.

Handlungsorientierung in der Ausbildung von Lehrkräften und pädagogischen Fachkräften. Konzeptionen und Forschungsperspektiven
Eine zentrale Herausforderung in der Professionalisierung pädagogischer Fach- und Lehrkräfte besteht in der Relation von eher theoretischen und praktischen Ausbildungsbestandteilen. Beispielsweise fühlen sich angehende Lehrkräfte durch ihr Studium häufig nicht ausreichend auf die beruflichen Anforderungen vorbereitet. Daher wird verstärkt versucht, Curricula von Ausbildungs- und Studiengängen deutlicher an den tatsächlichen professionellen Handlungsanforderungen zu orientieren und auch in frühen Ausbildungsphasen verstärkt Elemente beruflicher Praxis zu integrieren. Dieser Band nimmt die Handlungsorientierung in der Ausbildung von Lehrkräften und pädagogischen Fachkräften theoretisch-konzeptionell sowie empirisch in den Blick. Zudem werden innovative Lehransätze aufgezeigt, die den Fokus auf eine Stärkung einer solchen Handlungsorientierung legen, z.B. durch simulationsbasierte Lern- und Prüfungsformate. Es handelt sich um den zweiten Band der Reihe Paderborner Beiträge zur Bildungsforschung und Lehrkräftebildung, die von der PLAZ – Professional School of Education herausgegeben wird.